Long-Term Regeneration and Functional Recovery of a 15 mm Critical Nerve Gap Bridged by Tremella fuciformis Polysaccharide-Immobilized Polylactide Conduits. (21st August 2013) - Hsu, Shan-hui; Chan, Shan-Ho; Weng, Chih-tsung; Yang, Shu-Hui; Jiang, Ching-Fen
Abstract : Novel peripheral nerve conduits containing the negatively charged Tremella fuciformis polysaccharide (TF) were prepared, and their efficacy in bridging a critical nerve gap was evaluated. The conduits were made of poly(D, L-lactide) (PLA) with asymmetric microporous structure. TF was immobilized on the lumen surface of the nerve conduits after open air plasma activation. The TF-modified surface was characterized by the attenuated total reflection Fourier-transformed infrared spectroscopy and the scanning electron microscopy. TF modification was found to enhance the neurotrophic gene expression of C6 glioma cells in vitro. TF-modified PLA nerve conduits were tested for their ability to bridge a 15 mm gap of rat sciatic nerve. Nerve regeneration was monitored by the magnetic resonance imaging. Results showed that TF immobilization promoted the nerve connection in 6 weeks. The functional recovery in animals receiving TF-immobilized conduits was greater than in those receiving the bare conduits during an 8-month period. The degree of functional recovery reached ~90% after 8 months in the group of TF-immobilized conduits.